(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to verify the predominance of the type of muscular fiber through the dermatoglyphic. The sample was composed for 15 individuals, integrant athletes of the Brazilian Election of Canoeing Slalom, with average age of 17,9 ± 3,29 years and following measured the anthropometrics ones: weight 65,4 ± 6,47, stature 1,70 ± 6,16. For the determination of the type of fiber the Dermatoglyphics method was used, of Cummins and Midlo, 1942 apud Fernandes Filho, to get the type of drawing of the fingerprints (SQTL =140,3 ± 39,9; D10 = 12,2 ± 2,14; L>W=46,7%; L=W=20%; 10L=13,3%, AL=13,3% and ALW=6,7%). The used statistical treatment was the description. The results had allowed in accordance with concluding that the athletes of the Brazilian Election of Canoeing Slalom present, Dermatoglyphics parameters, glicolytics staple fiber predominance in relation the oxidative. One suggests that for the raised joined number of SQTL; a predominance of the fast glicolytics fiber in relation to the slow glicolytics fiber exists.